Towards a FrameNet Resource for the Legal Domain - Giulia Venturi; Alessandro Lenci; Simonetta Montemagn; Eva Maria Vecchi; Maria Teresa Sagri; Daniela Tiscornia (Proceedings of the Third Workshop on Legal Ontologies and Artificial Intelligence Techniques, 2009)
In the AI and Law community, the importance of frame-based ontologies has been acknowledged since the early 90's with the Van Kralingen's proposal of a frame language for legal knowledge representation. This still appears to be a strongly felt need within the community. In this paper, we propose to face this need by developing a FrameNet resource for the legal domain based on Fillmore's Frame Semantics, whose final outcome will include a frame-based lexical ontology and a legal corpus annotated with frame information. In particular, the paper focuses on methodological and design issues, ranging from the customization and extension of the general FrameNet for the legal domain to the linking of the developed resource with already existing Legal Ontologies.